DEVELOPMENT TRAINING EMPLOYERS' GROUP BAMBOO - Siti Khadijah Hidayati Nasution; Sinar Indra Kesuma; Suzanna Fitriany Sitepu (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2017)
Bamboo craft employers' group (Mr. Gunawan and Irwansyah), both located in the Village of West Rambung, District of South Binjai, Binjai. Both drying bamboo by using sunlight so that the quality is low if production during bad weather or rain, employers also do not yet know how to control the quality of the end product of bamboo, not knowing about the Patent/IPR, has not been able to make bookkeeping, and difficulty getting bamboo. Therefore, a team of lecturer from the Department of Agribusiness and Agroecotechnologi USU nurture small businesses through service activities: manufacture Oven Dryer, technology training drying bamboo by using Oven Dryer, training Quality Circles, training on Patent and IPR, making training books, and training Aquaculture Bamboo. The result: the entrepreneur has been able to use the oven dryer to dry the bamboo, to understand how to control the quality of the final product bamboo, know about the patent and intellectual property rights, are able to make bookkeeping, and know the techniques of bamboo cultivation right and can produce bamboo production / productivity and a high quality and sustainable. With the completion of this activity, both partners can develop their business and ultimately increase revenue. Outputs training: Oven Dryer, appropriate technology module bamboo drying, and appropriate technology module bamboo cultivation.